PPARs in the Control of Uncoupling Proteins Gene Expression. (26th November 2006) - Villarroya, Francesc; Iglesias, Roser; Giralt, Marta
Abstract : Uncoupling proteins (UCPs) are mitochondrial membrane transporters involved in the control of energy conversion in mitochondria. Experimental and genetic evidence relate dysfunctions of UCPs with metabolic syndrome and obesity. The PPAR subtypes mediate to a large extent the transcriptional regulation of the UCP genes, with a distinct relevance depending on the UCP gene and the tissue in which it is expressed. UCP1 gene is under the dual control of PPARγ and PPARα in relation to brown adipocyte differentiation and lipid oxidation, respectively. UCP3 gene is regulated by PPARα and PPARδ in the muscle, heart, and adipose tissues. UCP2 gene is also under the control of PPARs even in tissues in which it is the predominantly expressed UCP (eg, the pancreas and liver). This review summarizes the current understanding of the role of PPARs in UCPs gene expression in normal conditions and also in the context of type-2 diabetes or obesity.